Increased expression of receptor for activated C kinase 1 in temporal lobe epilepsy. (26th February 2015) - Xu, Xin; Yang, Xiaoyan; Xiong, Yan; Gu, Juan; He, Changlong; Hu, Yida; Xiao, Fei; Chen, Guojun; Wang, Xuefeng
Abstract Mesial temporal lobe epilepsy (MTLE) is characterized by spontaneous recurrent complex partial seizures. Increased neurogenesis and neuronal plasticity have been reported in animal models of MTLE, but not in detail in human MTLE cases. Here, we showed that receptor for activated C kinase 1 (RACK1) was expressed in the hippocampus and temporal cortex of the MTLE human brain. Interestingly, most of the cells expressing RACK1 in the epileptic temporal cortices co‐expressed both polysialylated neural cell adhesion molecules, the migrating neuroblast marker, and the beta‐tubulin isotype III, an early neuronal marker, suggesting that these cells may be post‐mitotic neurons in the early phase of neuronal development. A subpopulation of RACK1‐positive cells also co‐express neuronal nuclei, a mature neuronal marker, suggesting that epilepsy may promote the generation of new neurons. Moreover, in the epileptic temporal cortices, the co‐expression of both axonal and dendritic markers in the majority of RACK1‐positive cells hints at enhanced neuronal plasticity. The expression of β‐tubulin II (TUBB2B) associated with neuronal migration and positioning, was decreased. This study is the first to successfully identify a single population of cells expressing RACK1 in the human temporal cortex and the brain of the animal model, which can be up‐regulated in epilepsy. Therefore, it is possible that these cells are functionally relevant to the pathophysiology of epilepsy. <boxed-text content-type="graphic" id="jnc13052-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Mesial temporal lobe epilepsy is associated with increased neurogenesis and neuronal plasticity. We demonstrate expression of receptor for activated C kinase 1 (RACK1) and other markers associated with neuronal migration, synaptic plasticity and neurogenesis in the epileptic human and animal brains. The expression of tubulin, beta 2B class IIb (TUBB2B), associated with neuronal migration was decreased. Our findings raise the possibility that RACK1 is functionally relevant in epilepsy pathophysiology.